(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
It is necessary for a dosage form to maintain their chemical, physical, microbiological and toxicological stability during their entire shelf life. Knowing the intrinsic stability of the chemical and the breakdown pathway of the dosage form is crucial for this reason. We have developed a straightforward analytical approach using HPLC-UV/MS for the simultaneous measurement of Bilastine and Montelukast, as well as the identification of their degradants in tablet formulation. This method is specific, linear, accurate, and robust. The narcotic compounds were broken down one by one. The Zorbax XDB C-18 column (150*4.6) mm, 5µ, with a mobile phase of Water:Acetonitrile:Formic acid (50:50:1), was used to achieve the separation. A flow rate of 1 ml/min was used with an injection volume of 20 µl. A UV-Vis Spectrophotometer was used for peak detection, while a mass spectrophotometer was employed for identification. Bilastine had a retention time of 3.22 minutes and Montelukast of 4.80 minutes. Proposed method was stability indicating, specific, linear, accurate and robust. The degradation pathway was established for Bilastine and Montelukast by studying their degradation in various stress conditions. The Bilastine was found stable in Photolytic and thermal degradation while there was degradation observed in Montelukast in all stress conditions.